ANALYSIS OF STOCK RETURNS BEFORE AND AFTER EID AL-FITR 2023 (EVENT STUDY ON SHARES OF DEPARTMENT STORE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - Siti Irmayanti; Wa Ode Rayyani; Amelia Rezki Septiani Amin (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study is a type of quantitative research with the aim of determining Stock Return before and after Eid al-Fitr in 2023. This study was conducted in 2023 with an observation period of 30 days, consisting of 15 days before and 15 days after Eid al-Fitr. This sample is taken from shares of companies in the Department Store industry listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is quantitative data with skunder data sources obtained from www.financeyahoo.com. The data analysis tools used in this study are normality test and paired sample t-test. Based on the results of data research using the Statistical Package for the Social Science (SPSS) version 29, it shows that there is no significant difference in stock returns on Department Store company stocks before and after Eid al-Fitr in 2023.